Dermoscopy in Leprosy: A Clinical and Histopathological Correlation Study - Alpana Mohta; Suresh Kumar Jain; Aditi Agrawal; Ramesh Kumar Kushwaha; Pritee Sharma; Khusbhoo Sethia; Manish Jain (Mattioli1885, 2021)
Background: Leprosy, an insidious infectious granulomatous disease, is diagnosed traditionally through clinical examination coupled with skin smears and histopathology. It has myriad clinical presentations that pose diagnostic challenges. Lately, dermoscopy has emerged as a rapid, noninvasive diagnostic modality for many dermatoses. Objectives: We evaluated the dermoscopic findings of various manifestations of leprosy and correlated them with clinical and histopathological features. Methods: This prospective, cross-sectional study was conducted in our skin outpatient department for a period of 1 year. Patients newly diagnosed as having leprosy or those undergoing leprosy treatment for less than 6 months were included. The most representative lesion was dermoscopically evaluated and later biopsied. Results: We included 73 patients in the study. Results indicated an obvious correlation between dermoscopic findings and histopathology. We noted orangish yellow and white structureless areas, steadily throughout the spectrum, depicting dermal granuloma. Additionally, we observed focal vascular structures such as branching, linear, and crown vessels that result from the pressure of granuloma pushing the dilated vessels upwards. The relative absence of skin appendages aided in differentiating leprosy from other granulomatous disorders. Novel findings of our study were the detection of a branch-like pattern of clofazimine-induced pigmentation on dermoscopy and orange globules on onychoscopy. Other unique findings included violaceous structureless areas, characteristic large telangiectatic vessels, follicular plugging, star-shaped silvery-white scaling, and white globules in type 1 reaction; white shiny steaks were observed in patients with borderline lepromatous leprosy, and central white dots and keratotic plugs were observed in patients with histoid leprosy. Conclusions: Dermoscopy, as a noninvasive modality, could aid in the quick diagnosis of leprosy and should be used as a handy tool to complement other investigative tools for this disease.